A Responsive Eswatini Secondary Schools Curriculum: What, How and Why Are We Teaching? - Dumisa C. Mabuza; Molyn M. Mpofu; Makhulu A. Makumane (E-Journal of Humanities, Arts and Social Sciences)
The current Eswatini secondary school curriculum may not be fully optimized to foster graduates who actively contribute to the advancement of knowledge as observed in some developed countries. This research critically examined the Eswatini secondary school curriculum to determine its responsiveness to the evolving needs of the nation. It delved into the fundamental questions of “what,” “how,” and “why” teaching is done in Eswatini’s secondary schools. Through a comprehensive analysis, the research explored the curriculum’s alignment with national development goals, its relevance to 21st-century skills, and its effectiveness in preparing students for the world of work. Employing a descriptive research design through semi-structured interviews, this study identified strengths, weaknesses, and gaps in the current curriculum. The study used teachers in science, agriculture and consumer sciences (n=12). Data was analysed using framework analysis. The study’s findings reveal a misalignment between the Eswatini curriculum, the evolving needs of the nation and global standards. The content appears to prioritize rote memorization of English terminology and basic concepts, lacking a clear progression toward higher levels of learning. Eswatini curriculum’s potential obsolescence and lack of adaptation to theoretical advancements. Furthermore, the research highlights the necessity for curriculum reform. By advocating for a curriculum responsive to the demands of the 21st century, stakeholders can strive to equip future graduates with the necessary competencies and adaptability to thrive in a rapidly changing world. This study reveals a misalignment between the Eswatini curriculum and national development goals, 21st-century skills, and the demands of the modern workplace, advocating for curriculum reform to better prepare students for the future.